Ecofriendly and sustainable metal-free leather tanning using novel poly(carbamoyl sulfonate) technology - Pengfei Qiao; Jie Liu; Liqiang Jin; Feifei Zhang; Zhonghe Feng; Yulu Wang (Collagen and Leather)
Abstract Despite its potential as a metal-free tanning agent capable of eliminating Cr pollution in the leather industry, the conventional preparation of poly(carbamoyl sulfonate) faces challenges, such as the extensive use of low-boiling organic solvents and low blocking ratios of –NCO groups. Herein, a liquid sulfonate chain extender, 2,3-dihydroxypropanesulfonic acid triethylamine salt (DHPSTEA), was initially synthesized. A series of poly(carbamoyl sulfonate) tanning agents (CTAS) were then synthesized using DHPSTEA and various diisocyanates as reaction monomers, with sodium bisulfite serving as the blocking agent and without utilizing organic solvents. CTAS demonstrated a blocking ratio of > 99% and satisfactory stability under acidic conditions at room temperature. Application experiments revealed that CTAS exhibited excellent tanning performance, with the parent diisocyanate monomer markedly influencing their tanning properties. CTAS synthesized with dicyclohexylmethane-4,4′-diisocyanate resulted in optimal product performance, yielding a shrinkage temperature of 83.2 °C at a 6% dosage. CTAS-tanned leather displayed excellent collagen fiber dispersion, yellowing resistance and mechanical properties. Additionally, CTAS is easy to biodegrade (BOD5/COD > 0.45). Thus, this novel metal-free tanning agent holds a great potential as a sustainable alternative to traditional chrome tanning agent. Graphical Abstract